Central banking in an era of quantitative easing - Andrew Sheng (Levy Economics Institute of Bard College, 2011)
This paper reviews the key insights of Hyman P. Minsky in arguing why finance cannot be left to free markets, drawing on the East Asian development experience. The paper suggests that Minsky's more complete stock-flow consistent analytical framework, by putting finance at the center of analysis of economic and financial system stability, is much more pragmatic and realistic compared to the prevailing neoclassical analysis. Drawing upon the East Asian experience, the paper finds that Minsky's analysis has a system-wide slant and correctly identifies Big Government and investment as driving employment and profits, respectively. Specifically, his two-price system can aid policymakers in correcting the systemic vulnerability posed by asset bubbles. By concentrating on cash-flow analysis and funding behaviors, Minsky's analysis provides the link between cash flows and changes in balance sheets, and therefore can help identify unsustainable Ponzi processes. Overall, his multidimensional analytical framework is found to be more relevant than ever in understanding the Asian crisis, the 2008 global financial crisis, and policymaking in the postcrisis world.
Keywords: B26; E12; G28; 330; financial economics; Keynes; Keynesian; post-Keynesian; government policy and regulation